Affiliation with substance‐using peers: Examining gene‐environment correlations among parent monitoring, polygenic risk, and children's impulsivity. Issue 5 (31st May 2017) - Elam, Kit K.; Chassin, Laurie; Lemery‐Chalfant, Kathryn; Pandika, Danielle; Wang, Frances L.; Bountress, Kaitlin; Dick, Danielle; Agrawal, Arpana
Abstract: Parental monitoring can buffer the effect of deviant peers on adolescents' substance use by reducing affiliation with substance‐using peers. However, children's genetic predispositions may evoke poorer monitoring, contributing to negative child outcomes. We examined evocative genotype‐environment correlations underlying children's genetic predisposition for behavioral undercontrol and parental monitoring in early adolescence via children's impulsivity in middle childhood, and the influence of parental monitoring on affiliation with substance‐using peers a year and a half later ( n  = 359). Genetic predisposition for behavioral undercontrol was captured using a polygenic risk score, and a portion of passive rGE was controlled by including parents' polygenic risk scores. Children's polygenic risk predicted poorer parental monitoring via greater children's impulsivity, indicating evocative rGE, controlling for a portion of passive rGE. Poorer parental monitoring predicted greater children's affiliation with substance‐using peers a year and a half later. Results are discussed with respect to gene‐environment correlations within developmental cascades.